Comparison of the different controlling techniques for buck converter in LED application - Shwetha DV; Lakshman Rao S. Paragond (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper recounts the design and construction of various controlling techniques for buck converter. If the designed controller for any converter is not proper which leads to high overshoot and steady state error, and its dynamic response varies with changes in load, especially at high load current conditions. The lead-lag controller for the converter  is desgined using classical control theory ,Bode Plot technique is used to examine the stability of the system.By using deravetive part of the PID controller on output signal instead of voltage error signal,this combination of control technique reduces the overshoot and settling time,and how the transient response will be affected if deravetive controller is in the forward path.